Avascular Osteonecrosis in Systemic Sclerosis Patient: Risk Factors and Role of Vasculopathy? - Safarina Kharima Laitupa; Perdana Aditya Rahman (Indonesian Journal of Rheumatology, 2022)
Avascular Necrosis (AVN) or osteonecrosis refers to the death of osteocytes and osteoblasts. Sites such as the femoral head, the head of the humerus and the mandibular with restricted access to local blood supply are particularly vulnerable to osteonecrosis. Various traumatic and non-traumatic causes of AVN are known, including systemic autoimmune diseases. Among traumatic causes, physical trauma, decompression sickness or radiation may be cited. In the non-trauma cases, two theories are disputed: the first concerns the occurrence of an intravascular coagulation and the second one attributes the ischemia to extravascular compression. AVN has been well described in patients with autoimmune diseases such as systemic lupus erythematosus, but in systemic sclerosis (SSc) patients, there have been limited case reports and case series. We present a case of a 32-year old woman with systemic sclerosis on corticosteroid and avascular osteonecrosis and elaborating possible etiologies or mechanism of avascular osteonecrosis in SSc.